Produced by Irving Thalberg : theory of studio-era filmmaking - Salzberg, Ana (Edinburgh : Edinburgh University Press, 2020)
Drawing on archival sources, this is the first book to explore Thalberg's insights into casting, editing, story composition and the importance of the mass audience from a theoretical perspective.
Intro -- Acknowledgments -- 1. Opening credits -- 2. Oblique casting and early MGM -- 3. One great scene: Thalberg's silent spectacles -- 4. Entertainment value and sound cinema -- 5. Love stories and general principles: the development of the production code -- 6. The intelligent producer and the restructuring of MGM -- 7. "What can we do to make the picture better?" -- 8. Conclusion: Once a star, always a star -- Works cited -- Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 8, 2020).
JSTOR
Keywords: Thalberg, Irving G., -- 1899-1936.; Thalberg, Irving G., -- 1899-1936; Motion picture producers and directors -- United States -- Biography; Motion picture industry -- United States -- History; Producteurs et réalisateurs de cinéma -- États-Unis -- Biographies; Cinéma -- Industrie -- États-Unis -- Histoire; PERFORMING ARTS -- Film & Video -- Direction & Production; Motion picture industry; Motion picture producers and directors; United States; Biography; Biographies; History; Biographies; Biographies